Engineering with Excel - Larsen, Ronald W. (Pearson, 2014)
Based on¿Excel 2010, Engineering with Excel, 4e¿ takes a comprehensive look at using Excel in engineering.¿ This book focuses on applications and is intended to serve as both a textbook and a reference for students.